Transcriptome analysis indicates improved adipose tissue function in growing Iberian pig fed olive by-products based diets - Palma-Granados, Patricia; García-Casco, Juan M.; Peiró-Pastor, Ramón; Óvilo, Cristina; Delgado, Miguel A.; García, Fabián; López-García, Adrián; González, Elena; Muñoz, María (Frontiers in Genetics, 2025)
Supplementing diets with olive by-products offers promising benefits for alleviating animal stress caused by feed restriction without compromising growth. The aim of this study was to explore the transcriptome of backfat in Iberian pigs fed experimental diets based in olive by-products. This study involved 15 pigs, which were placed into three diet groups: a Control (C) group, a dry olive pulp (DOP) group, which was fed a compound feed elaborated with olive pulp, and a wet crude olive cake (WCOC) group, which was fed a compound feed and an olive cake silage provided ad libitum. The pigs were fed these diets for 191 days, and at a body weight of 95 kg, backfat biopsies were taken, and transcriptome analyses were performed on 5 animals per group. Compared to the C group, we identified 411 and 924 differentially expressed genes (DEG; q < 0.05, |Fold Change|>1.5) for DOP and WCOC diets, respectively. In the DOP diet, functions related to polysaccharides metabolism were significantly activated, while the WCOC exhibited activated biological processes associated with apoptosis and cellular death. Both supplemented diets showed inhibition of functions involved in inflammatory and immune responses, as well as reactive oxygen species production. Furthermore, in the WCOC diet, functions related to cholesterol and lipid metabolism were repressed. In both comparisons, the ADIPOQ gene played a key role in the majority of affected functions. Our findings suggest that olive by-products may enhance adipose tissue function, which could have positive implications for animal health.